2010
DOI: 10.1080/10408391003626223
|View full text |Cite
|
Sign up to set email alerts
|

Intake of Added Sugars and Selected Nutrients in the United States, National Health and Nutrition Examination Survey (NHANES) 2003—2006

Abstract: In the Institute of Medicine (IOM) macronutrient report the Committee recommended a maximal intake of < or = 25% of energy from added sugars. The primary objectives of this study were to utilize National Health and Nutrition Examination Survey (NHANES) to update the reference table data on intake of added sugars from the IOM report and compute food sources of added sugars. We combined data from NHANES with the United States Department of Agriculture (USDA) MyPyramid Equivalents Database (MPED) and calculated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
167
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(185 citation statements)
references
References 50 publications
13
167
0
5
Order By: Relevance
“…The hypocaloric diets employed in the current research utilized added sugar consumption levels at the 25 th and 50 th percentile of consumption in the American diet [50]. Whether these findings would hold for a diet containing higher levels of added sugar would represent an important topic for future research.…”
Section: Discussionmentioning
confidence: 99%
“…The hypocaloric diets employed in the current research utilized added sugar consumption levels at the 25 th and 50 th percentile of consumption in the American diet [50]. Whether these findings would hold for a diet containing higher levels of added sugar would represent an important topic for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these observations, the current Guidelines of Nutrition and Health Recommendations suggest that a healthy diet must provide no more than 5% of total energy intake as simple sugars. In contrast, currently the 13% of the American population consumes over 25% of the daily energy intake as sugar [3].…”
Section: Sugars Consumption In Modern Societymentioning
confidence: 99%
“…148 Consumption of SSBs is currently the single largest category of caloric intake in children, accounting for 10% to 15% of their total daily calories. [149][150][151] Data from the 2010 National Youth Physical Activity and Nutrition Study found that high school students consumed ≥1 SSBs daily, including regular soda (25%), a serving of a sports drink (16%), and another SSB (17%). 152 In a trend and cross-sectional analysis from the NHANES for the period from 1999 to 2000 through 2007 to 2008, the prevalence of heavy SSB consumption (≥500 kcal/d) increased among children (4% to 5%) but decreased among adolescents (22% to 15%) and young adults (29% to 20%).…”
Section: Sugar-sweetened Beveragesmentioning
confidence: 99%